Self-assembly of Pd(II) pyrazolyl complexes to 1-D hydrogen-bonded coordination polymers - Netto, AVG; Frem, RCG; Mauro, Antonio Eduardo [UNESP]; de Almeida, E. T.; Santana, A. M.; de Souza, J.; Santos, RHA (Elsevier B.V., 2003)
This work describes the synthesis and characterization of two novel Pd(II) pyrazolyl complexes of the type [PdX2(HdmPz)(2)](n) {X=SCN- (1), N-3(-) (2); HdmPz=3,5-dimethylpyrazole} that self-assemble through N-H...NCS or N-H...NNN hydrogen bonds to yield infinite one-dimensional chains, as confirmed by single crystal X-ray study on 1. The expected solid state polymeric structure for 2 is slowly broken up in CHCl3 Solution, leading to an equilibrium mixture of cis and trans-[Pd(N-3)(2)(HdmPz)(2)] monomers, as demonstrated by time-dependent IR and NMR studies. (C) 2003 Elsevier B.V. B.V. All rights reserved.
Keywords: Pd(II) pyrazolyl complexes; pseudohalide; self-assembly; coordination polymers